Emission measurements of alkenes, alkanes, SO2, and NO2 from stationary sources in Southeast Texas over a 5 year period using SOF and mobile DOAS. Issue 4 (27th February 2014) - Johansson, John K. E.; Mellqvist, Johan; Samuelsson, Jerker; Offerle, Brian; Lefer, Barry; Rappenglück, Bernhard; Flynn, James; Yarwood, Greg
Abstract A mobile platform for flux measurements of VOCs (alkanes and alkenes), SO2, and NO2 emissions using the Solar Occultation Flux (SOF) method and mobile differential optical absorption spectroscopy (DOAS) was used in four different studies to measure industrial emissions. The studies were carried out in several large conglomerates of oil refineries and petrochemical industries in Southeast and East Texas in 2006, 2009, 2011, and 2012. The measured alkane emissions from the Houston Ship Channel (HSC) have been fairly stable between 2006 and 2011, averaging about 11, 500 kg/h, while the alkene emissions have shown greater variations. The ethene and propene emissions measured from the HSC were 1511 kg/h and 878 kg/h, respectively, in 2006, while dropping to roughly 600 kg/h for both species in 2009 and 2011. The results were compared to annual inventory emissions, showing that measured VOC emissions were typically 5–15 times higher, while for SO2 and NO2 the ratio was typically 0.5–2. AP‐42 emission factors were used to estimate meteorological effects on alkane emissions from tanks, showing that these emissions may have been up to 35–45% higher during the studies than the annual average. A more focused study of alkene emissions from a petrochemical complex in Longview in 2012 identified two upset episodes, and the elevation of the total emissions during the measurement period due to the upsets was estimated to be approximately 20%. Both meteorological and upset effects were small compared to the factor of 5–15, suggesting that VOC emissions are systematically and substantially underestimated in current emission inventories.